Penguatan Civil Society Organizations untuk Eliminasi AIDS, TB, Malaria (ATM) dan Ketahanan Bencana di Kabupaten Serdang Bedagai - Ruslan Zuhair Pulungan; Syahferi Anwar; Solihin Solihin; Balqis Nurmauli Damanik (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
This community service activity aims to strengthen civil society organizations (CSOs) in the efforts to eliminate AIDS, tuberculosis (TB), and malaria (ATM), as well as to enhance disaster resilience in Serdang Bedagai Regency. Through a participatory approach, the program involves local communities in outreach, training, and the development of CSO networks focused on health issues and disaster mitigation. The activities began with an analysis of the community health situation and needs assessment, followed by education on the prevention of infectious diseases and disaster risk management. The results of the program implementation indicate an increase in community awareness regarding the importance of health and disaster preparedness, as well as the establishment of stronger collaboration among various community elements. By empowering CSOs, it is expected that a healthier and more resilient environment will be created, thereby reducing the impact of infectious diseases and natural disasters. This program not only provides direct benefits to the community but also builds sustainable local capacity to face future health and disaster challenges.